Parmenides’ Poem: Riddle from B 5 - Bogaczyk-Vormayr, Małgorzata (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2016)
The paper constitutes a short analysis of the poem of Parmenides from Elea “On Nature”. The author posits that this text is the original aim of ontology. In the author’s opinion, the most important thesis of the poem is to be found in the fragment B 5, in which she recognizes the ancient motive of the self-knowledge (“the inner Way of Truth”). The primary purpose of the analysis is to interpret the mythological language and to reconsider terminology, e.g. Way of Day and Way of Night, Dike and Moira, thymos, plankton noon. Furthermore, the thinking of Parmenides is briefly interpreted in comparison with Heraclitus, Anaximander, and Archytas.
Keywords: Parmenides; ontology; Way of Truth; pistis alethes; thymos; peras